Lymphocytic Mastopathy - Entity with Diagnostic Dilemma: A Case Report: Life Sciences-Pathology - Pavithra, Dr.M.; Thanka, Dr.J.; .Manikandan, Dr (International Journal of Life Science and Pharma Research, 2022)
Lymphocytic mastopathy is a condition that affects the breasts of people who have had diabetes for a long time. It frequently manifests as huge hard lumps, raising cancer risk and necessitating unnecessary surgery. Histopathologically, it is characterized by sclerosing lymphocytic mastitis. A nulliparous woman appeared with a firm, palpable breast lump. Malignancy was the clinical impression. They conducted imaging tests, which confirmed a malignancy suspicion. Histopathology revealed sclerosing fibrosis with keloid-like characteristics and abundant per lobular and intralobular lymphocytic infiltrates. Most of these instances will be resolved by clinicopathological correlation, which will help to avoid invasive surgical operations. However, imaging studies may not be appropriate in many situations. Understanding this pathology's proclivity is crucial because it shares many clinical and radiological features with breast cancer. Here we report a unique case study of Lymphocytic mastopathy in a 44-year-old female patient with complaints of pain in the right breast for 15 days. Ultrasonograms and histopathological studies have been conducted, which evidenced lymphocytic mastopathy.